Gambaran Budaya Organisasi Pada Karyawan Di Universitas Potensi Utama - Rodia Afriza; Nur Anzelina Hrp (Asosiasi Riset Ilmu Kesehatan Indonesia, 2023)
This study aims to determine the description of organizational culture in employees at the Potential Utama University. This type of research uses a descriptive quantitative approach, namely analyzing data by describing or describing the collected data as they are without intending to make conclusions that apply to the public or generalizations. The population in this study amounted to 158 people. The sample of this study was 30 people. The technique used is non-probability sampling using purposive sampling. The results of this study indicate a scoring result of 1149.8 which refers to the aspect of tolerance for conflict which is indicated by a significant value (Sig. 2 Tailed) of 0.02 (P <0.05) and a Correlation Coefficient value of 0.539. This means that the organizational culture at the Potential Utama University applies an attitude of tolerance, which makes the employees of the Potential Utama University feel they have the space to express opinions and ideas.